2016
DOI: 10.1002/ajh.24526
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in patients with hematologic malignancy and thrombocytopenia

Abstract: The optimal management of hematologic malignancy-associated venous thromboembolism (VTE) in patients with moderate-to-severe thrombocytopenia is unclear. This is a retrospective study of 128 adult patients with hematologic malignancies who were diagnosed with VTE. The outcome of patients with significant thrombocytopenia (≤50,000/µL) was compared with those without. Forty-seven patients (36.7%) had a platelet count ≤50,000/µL during a period of time of perceived need for new or continued anticoagulation. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 30 publications
3
59
0
2
Order By: Relevance
“…The patient with thrombocytopenia is another challenge, as clear-cut instructions and thresholds for the use of different agents are absent. Most clinicians would use the empirical cut off of 50,000/mm 3 for the administration of full LMWH administration and would half the dose for platelet counts between 49,000 and 30,000 mm 3 [103][104][105]. Based again on clinical experience, DOAC administration is considered safe at platelet counts of >50,000/mm 3 when the indication is treatment of VTE and at >75-80.000/µL when the indication is prophylaxis [106].…”
Section: Thromboprophylaxis: To Doac or Not To Doac?mentioning
confidence: 99%
“…The patient with thrombocytopenia is another challenge, as clear-cut instructions and thresholds for the use of different agents are absent. Most clinicians would use the empirical cut off of 50,000/mm 3 for the administration of full LMWH administration and would half the dose for platelet counts between 49,000 and 30,000 mm 3 [103][104][105]. Based again on clinical experience, DOAC administration is considered safe at platelet counts of >50,000/mm 3 when the indication is treatment of VTE and at >75-80.000/µL when the indication is prophylaxis [106].…”
Section: Thromboprophylaxis: To Doac or Not To Doac?mentioning
confidence: 99%
“…Furthermore, prolonged thrombocytopenia (> 30 days) in patients with CAT is associated with a greater than four‐fold increased risk of recurrent venous thromboembolism (VTE) . The rates of bleeding in this population range from 7% to 33%, and the rates of recurrent thrombosis range from 10% to 44% . In 2013, the ISTH Scientific and Standardization Committee on Haemostasis and Malignancy released a guidance document addressing the management of challenging cases of patients with CAT, including CAT in the setting of thrombocytopenia .…”
Section: Scope and Methodologymentioning
confidence: 99%
“…Although a number of observational studies have reported on one management strategy or the other [11][12][13][14], only a handful of studies have reported data on several approaches. Unfortunately, randomized comparisons are not available, and clinicians are left with only retrospective case series and small, observational cohort studies to guide clinical decision-making [6,7,15]. A recent systematic review of the literature failed to identify any evidence for superiority of one method over another [16].…”
Section: Background and Available Evidencementioning
confidence: 99%
“…ISSN: 2379-4550 http://digitalcommons.wayne.edu/crp, © 2019 The Author(s) 4 Licensed under Creative Commons Attribution Non-Commercial 4.0…”
Section: Clinical Applicationmentioning
confidence: 99%
“…This drug was not feasible for an outpatient, long-term use in our patient. 4 Aside from this critical appraisal's chosen publication, the Wang paper is the only other study examining anticoagulation in atrial fibrillation patients with thrombocytopenia. However, it is a retrospective cohort study assessing safety and efficacy of DOAC vs warfarin therapy in atrial fibrillation patients with thrombocytopenia.…”
mentioning
confidence: 99%